Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Answer:
Step-by-step explanation:The solution to the system of equations are;
x = -4/3
y = 5/3
Step-by-step explanation:
To find the Solution, we would carry the Operation simultaneously.
4x + 2 = -2y .........(i)
6y - 18 = 6x ..........(ii)
First let's rearrange the equations, to make the journey smoother
2y + 4x = -2 ...........(iii)
6y - 6x = 18 ...........(iv)
Let's Multiply equation (III) by 3 so as to have a uniform spot to begin elimination.
3.2y + 3.4x = -2 . 3
6y + 12x = -6............... (v)
Let's subtract equation (v) from equation (iv)
= 0y - 18x = 24
-18x = 24
x = - 24 / 18
x = -4/3
Let's substitute (x = -4/3) in equation (ii), so that we can solve for the value of y:
6y - 18 = 6x
6y - 18 = 6 (-4/3)
6y - 18 = -8
6y = -8 + 18
6y = 10.
y = 10 / 6
y = 5/3
The solution to the system of equations are;
x = -4/3
y = 5/3
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.